Assessing Causes of Driver Job Dissatisfaction in the Flatbed Motor Carrier Industry - Ashley Wygal; Douglas Voss; Michael B. Hargis; Scott Nadler (Logistics)
Trucking companies play a critical role in the U.S. economy but face many challenges. The trucking industry’s greatest challenge may be the persistent driver turnover problem. Trucking companies regularly report turnover rates exceeding 100%. Each driver costs between $2200–$21,000 to replace and new drivers often impact carrier customer service and safety performance. The purpose of this article is to qualitatively explore the challenges drivers face with hopes of uncovering unique methods to improve job satisfaction and ameliorate turnover and retention issues. Results indicate that driver job satisfaction is related to compensation, management quality, equipment quality, home time, and wait time. Proactive managerial actions in the form of pre-planning loads are proposed as a method for carriers to resolve many driver concerns and possibly provide carriers with a competitive advantage in driver retention.